Valeo-pedagogical culture of parents and its role in forming healthy way of life of preschool age children - Voloshyn O. R. (Kharkov National Pedagogical University, 2012)
It is considered organizationally-methodical aspects of work with family on forming health for young people. Maintenance is reflected, forms of organization of work with families in the conditions of valeology of preschool education. In research were questionnaire 45 parents, 25 educators and 25 children in the free mode during two weeks. The results of questionnaires proved that only 20% parents spare certain attention in families to forming of healthy way of life of children, 30% consider that an example of adults in this question is fundamental principle, but almost 68% parents have an insufficient level of pedagogical valeological culture. The analysis of results of questionnaire of children testifies that respondents have necessary pre-conditions for forming knowledge, abilities and skills of healthy way of life, accessible understanding of value of own health and health of near them. Methodical recommendations are brought for activations of co-operation of preschool educational establishment and family on forming of health of preschool children.